#TITLE_ALTERNATIVE# - (NIM 13203151), PRAWIRA
The increasing of electric power demand must be balanced with improvement of energy system reliability, in this case is power availability. Power availability in electric power system must be enough to serve the load system requirement. The possibility of system that cannot serve load, expressed with index of unserved energy and LOLP (loss of load probability). There are several ways that we can do to guarantee power availability in the system. In this study, the effort is limited by adding some power plants in DKI Jakarta and Tangerang system to guarantee power availability based on LOLP until next 10 years. Calculation of LOLP value at this study applies segmentation method. Power plants is added at the time of LOLP exceed standard value which specified 1 day/year. Power plant capacity which must be added got with effective capacities of generator calculation approach. The time and capacity variables will be consideration to determine type of power plants that should be built in DKI Jakarta and Tangerang.